Confession and retraction: the application of Islamic legal maxims in Safiyyatu and Amina’s cases in Northern Nigeria - Zakariyah, Luqman (Routledge Taylor & Francis Group, 2010)
The legal procedural system of the Islamic law has been constructively or destructively mounted with criticisms. One of the reasons for these criticisms is assumingly based on the lack of incorporating the objective of the Islamic Law through “intertexualizing” the textual evidences on one hand and failure to extrapolate all sources available for “dynamizing” the legal system of the Sharicah (Islamic law) on the other. The criticisms that trailed Amina Lawal and Safiyyatu Husaini’s cases in Nigeria are, in our opinion, based on the above phenomenon. “Islamic legal maxims” as a subject is one of the sciences which aphoristically subsume all the spectrums promoted by the Sharicah. In Islamic jurisprudence, there are many legal maxims, including legal maxims of confession and retraction, on which the tenets of Islamic law are based. This article focuses on how these legal maxims can be explored to ensure justice in Islamic criminal procedures, as it is established that confession is recommendable in crimes that involve rights of men as opposed to crimes that involve rights of God, in which confession is detestable. Some of the questions raised in this article are; is it possible for someone to confess to a criminal act and to retract later? When is retraction of confession allowed in Islamic judiciary procedure? What is the effect of retraction? And in what offences can retraction avert the punishment assigned to the offence?